2011
DOI: 10.1021/ie200267n
|View full text |Cite
|
Sign up to set email alerts
|

Defects and Minor Phases in O+ and Zr+ Ion Co-implanted SrTiO3

Abstract: This article reports on a comprehensive experimental study of 16O+ and 90Zr+ ion co-implanted SrTiO3 (STO) single crystals. In this study, STO was used as a model material to simulate a waste form for disposal of radioactive 90Sr that decays to 90Y and subsequently to 90Zr by emission of β– particles. Sequential 16O+ and 90Zr+ ion implantation at 550 K was performed and Zr and O atomic concentrations of up to 1.5 atom % each in STO were achieved. A number of analytical methods were employed to characterize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…The substitutional Zr has seven chemical bonds with neighboring O atoms, including the extra one introduced into the structure. Although Zr is well aligned with the [001] axis (Figure 3c), in agreement with ionchanneling observations, 10 neither Zr nor O is located exactly at the original Sr site, which is again consistent with our previous observations. 10 There are several local minima for this defect, but the differences consist of minor rearrangements of the nearest oxygen atoms.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The substitutional Zr has seven chemical bonds with neighboring O atoms, including the extra one introduced into the structure. Although Zr is well aligned with the [001] axis (Figure 3c), in agreement with ionchanneling observations, 10 neither Zr nor O is located exactly at the original Sr site, which is again consistent with our previous observations. 10 There are several local minima for this defect, but the differences consist of minor rearrangements of the nearest oxygen atoms.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…Detailed experimental procedures and parameters were described elsewhere. 10 A cross-sectional thin specimen was prepared using a FEI Helios 600 Nanolab system of focused ion beam (FIB) and scanning electron microscope (SEM). Ga + ions at 30 and 5 keV were used for cutting and thinning the specimen, respectively, and Ar + ions were used at 1 keV (Fischione Nanomill) for removal of the damage layer produced by the Ga + ions.…”
Section: ■ Methodsmentioning
confidence: 99%
“…The data from the experimental study reported here may help understand various effects induced by 90 Sr decay on waste form properties and allow us to validate theoretical models and simulations. A part of the experimental data (Jiang 2011) reported here has been submitted for publication and the most recent ones, including TEM results, will be published in a later date.…”
Section: Theorymentioning
confidence: 99%
“…The microstructure of the irradiated fuel is complex due to various factors, including the presence of various fission product precipitates, β-decay induced changes in charge imbalance, increase in oxygen potential, temperature gradient, irradiation-enhanced GB migration, and lattice disorder produced by elastic collisions with high-energy neutrons and energetic daughter nuclide recoils in the damage cascade process. There is a long history of effort devoted to characterization of spent nuclear fuels.…”
Section: Introductionmentioning
confidence: 99%